Methane gas and its relationship with livestock activities in the province of Manabi, Ecuador - Luque Vera, Juan Carlos (2016)
The objective of the research was to determine the relationship between the quantity of cattle and methane emissions, in a study period of ten years, allowing to respond to the problem posed regarding the magnitude of CH4 emissions in the province. from Manabi. The study was based on the guides and guidelines issued by the intergovernmental panel on climate change, 2006, using the IPCC 2006 version 2.10 software. The results showed that CH4 emissions are considerably high, 531.68 Gg. CH4, highlighting enteric fermentation emissions, with approximately 50 times more methane than manure management emissions. Likewise, non-dairy cattle are responsible for a higher number of methane emissions compared to dairy cattle, in the case of enteric fermentation, with 287,724Gg. CH4, while for manure management, the highest emissions are generated by dairy cattle, with 7,217 Gg. of CH4. The hypothesis that there is an increase in methane emissions was accepted, due to the increase in the population of cattle.